2020
DOI: 10.1111/ene.14266
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with motoric cognitive risk syndrome in community‐dwelling older Chinese: a cross‐sectional study

Abstract: Background and purpose: A recently proposed pre-dementia syndrome, motoric cognitive risk (MCR) syndrome, is characterized by cognitive complaints and slow gait, and increases the risk of dementia and mortality. The aim of the present study was to explore the prevalence of and factors associated with MCR syndrome in elderly community-dwelling Chinese subjects. Methods: The Ningbo Community Study on Aging recruited 953 Chinese community-dwelling participants aged ≥ 65 years from November 2016 to March 2017. Han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
25
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 51 publications
10
25
3
1
Order By: Relevance
“…Walking speed was assessed by asking participants to walk a distance of 5 m at their usual pace, with a stopwatch used to measure time in seconds, and was calculated in metres per second. Consistent with previous studies, participants who were one standard deviation or more below the mean value for their age and sex were considered to have a slow walking speed [18,22] The cutoff values of slow walking speed in this study were as follows: men ≤74 years, ≤0.74 m/s; men 75–79 years, ≤0.64 m/s; men 80–84 years, ≤0.57 m/s; men ≥85 years, ≤0.56 m/s; women ≤74 years, ≤0.71 m/s; women 75–79 years, ≤0.59 m/s; women 80–84 years, ≤0.51 m/s; and women ≥85 years, ≤0.47 m/s.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Walking speed was assessed by asking participants to walk a distance of 5 m at their usual pace, with a stopwatch used to measure time in seconds, and was calculated in metres per second. Consistent with previous studies, participants who were one standard deviation or more below the mean value for their age and sex were considered to have a slow walking speed [18,22] The cutoff values of slow walking speed in this study were as follows: men ≤74 years, ≤0.74 m/s; men 75–79 years, ≤0.64 m/s; men 80–84 years, ≤0.57 m/s; men ≥85 years, ≤0.56 m/s; women ≤74 years, ≤0.71 m/s; women 75–79 years, ≤0.59 m/s; women 80–84 years, ≤0.51 m/s; and women ≥85 years, ≤0.47 m/s.…”
Section: Methodsmentioning
confidence: 97%
“…Walking speed was assessed by asking participants to walk a distance of 5 m at their usual pace, with a stopwatch used to measure time in seconds, and was calculated in metres per second. Consistent with previous studies, participants who were one standard deviation or more below the mean value for their age and sex were considered to have a slow walking speed [18,22] The cutoff values of slow walking speed in…”
Section: Motoric Cognitive Risk Syndrome Criteriamentioning
confidence: 99%
“…The frequency of nutrient intake was assessed based on the ingredient categories in the Dietary Guidelines for Chinese Residents (2016 edition) [20], that is, grains and potatoes, miscellaneous beans, soybean products, vegetables, fruits, nuts, edible fungi and algae, livestock and poultry meat, aquatic products, eggs and milk, and dairy products. Other lifestyle factors were coded "yes" if so, including current smoking and current alcohol drinking [21], and oral hygiene of received professional dental cleaning. Social function was assessed by Social Support Rate Scale (SSRS) [22].…”
Section: Demographics Lifestyle Activities and Social Supportmentioning
confidence: 99%
“…Their data formed the baseline data of this community-based cohort study. Detailed information of this study has been reported elsewhere [19]. The overall goal of the NCSA was to identify the health status of a community-dwelling elderly Chinese population and explore the helpful management and interventions for preventing geriatric diseases.…”
Section: Study Participantsmentioning
confidence: 99%